Double jeopardy from the COVID-19 pandemic: risk of exposure and income loss in Portugal - Ana Gama; Joana Alves; Daniela Costa; Pedro A. Laires; Patrícia Soares; Ana Rita Pedro; Marta Moniz; Luísa Solinho; Carla Nunes; Sónia Dias (BMC, 2021)
Abstract Background Increasing evidence indicates that the first wave of the COVID-19 pandemic had immediate health and social impact, disproportionately affecting certain socioeconomic groups. Assessing inequalities in risk of exposure and in adversities faced during the pandemic is critical to inform targeted actions that effectively prevent disproportionate spread and reduce social and health inequities. This study examines i) the socioeconomic and mental health characteristics of individuals working in the workplace, thus at increased risk of COVID-19 exposure, and ii) individual income losses resulting from the pandemic across socioeconomic subgroups of a working population, during the first confinement in Portugal. Methods This study uses data from 'COVID-19 Barometer: Social Opinion', a community-based online survey in Portugal. The sample for analysis comprised n = 129,078 workers. Logistic regressions were performed to estimate the adjusted odds ratios (AOR) of factors associated with working in the workplace during the confinement period and with having lost income due to the pandemic. Results Over a third of the participants reported working in the workplace during the first confinement. This was more likely among those with lower income [AOR = 2.93 (2.64-3.25)], lower education [AOR = 3.17 (3.04-3.30)] and working as employee [AOR = 1.09 (1.04-1.15)]. Working in the workplace was positively associated with frequent feelings of agitation, anxiety or sadness [AOR = 1.14 (1.09-1.20)] and perception of high risk of infection [AOR = 11.06 (10.53-11.61)]. About 43% of the respondents reported having lost income due to the pandemic. The economic consequences affected greatly the groups at increased risk of COVID-19 exposure, namely those with lower education [AOR = 1.36 (1.19-1.56)] and lower income [AOR = 3.13 (2.47-3.96)]. Conclusions The social gradient in risk of exposure and in economic impact of the pandemic can result in an accumulated vulnerability for socioeconomic deprived populations. The COVID-19 pandemic seems to have a double effect in these groups, contributing to heightened disparities and poor health outcomes, including in mental health. Protecting the most vulnerable populations is key to prevent the spread of the disease and mitigate the deepening of social and health disparities. Action is needed to develop policies and more extensive measures for reducing disproportionate experiences of adversity from the COVID-19 pandemic among most vulnerable populations.